2020
DOI: 10.1167/iovs.61.8.39
|View full text |Cite
|
Sign up to set email alerts
|

Energy Shortage in Human and Mouse Models ofSLC4A11-Associated Corneal Endothelial Dystrophies

Abstract: To elucidate the molecular events in solute carrier family 4 member 11 (SLC4A11)-deficient corneal endothelium that lead to the endothelial dysfunction that characterizes the dystrophies associated with SLC4A11 mutations, congenital hereditary endothelial dystrophy (CHED) and Fuchs endothelial corneal dystrophy 4. METHODS. Comparative transcriptomic analysis (CTA) was performed in primary human corneal endothelial cells (pHCEnC) and murine corneal endothelial cells (MCEnC) with normal and reduced levels of SLC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 77 publications
(105 reference statements)
2
15
0
Order By: Relevance
“…In the transcriptome analysis here, we observed gene expression alterations centered on cytoskeletal, membrane-associated, and ECM components in the mouse cornea. This work complements a recent transcriptomic analysis of cultured human CECs subjected to siRNA to reduce their SLC4A11 expression 28 and analysis of gene expression in human CEC 29 , 30 . Analysis of gene expression changes compensating for slc4a11 loss may be useful to identify molecular targets to treat FECD and CHED pathologic conditions.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the transcriptome analysis here, we observed gene expression alterations centered on cytoskeletal, membrane-associated, and ECM components in the mouse cornea. This work complements a recent transcriptomic analysis of cultured human CECs subjected to siRNA to reduce their SLC4A11 expression 28 and analysis of gene expression in human CEC 29 , 30 . Analysis of gene expression changes compensating for slc4a11 loss may be useful to identify molecular targets to treat FECD and CHED pathologic conditions.…”
Section: Introductionsupporting
confidence: 53%
“…SLC4A11 defects are recognized to manifest with compromised energy metabolism. In particular, strong evidence supports a role of SLC4A11 in facilitating CEC glutaminolysis in energy production 28 , 38 , 39 and suggested a role of SLC4A11 in uncoupling mitochondria to prevent oxidative damage 40 . In the present study, we identified seven expression alterations related to CEC energy metabolism (Table 3 , Suppl.…”
Section: Discussionmentioning
confidence: 96%
“… 9 A comparative transcriptome analysis performed in CHED primary CE cells and a mouse corneal endothelial cell line derived from Slc4a11 KO mice indicated a generalized inhibition of metabolic and transport gene expression in KO cells. 11 Oxidative stress appears to be a root cause of these changes since quenching mitochondrial ROS, mitochondrial uncoupling of KO cells, or circumventing glutaminolysis, all of which lower ROS production, rescue KO cells, and reverse corneal edema progression. 9 …”
mentioning
confidence: 99%
“…Human CHED samples are very rare. However, a recent study examined SLC4A11 localization in two CHED endothelial specimens and found that SLC4A11 was localized to the plasma membrane and did not overlap with an ER marker [ 44 ]. Thus, it appears that trafficking and localization studies are greatly influenced by expression system, and that the use of corneal endothelial tissue and/or primary cultured endothelial cells, although more challenging, would give unequivocal answers.…”
Section: Disease Associationsmentioning
confidence: 99%
“…Using comparative transcriptome analysis of primary cultures of human corneal endothelial cells and SLC4A11 KO MCEC (mouse corneal endothelial cells), Zhang et al [ 44 ] also found inhibition of cell metabolism, ion transport (e.g., SLC4A4-NBCe1), and mitochondrial function, along with the activation of AMPK-p53/ULK1, consistent with increased mitophagy and mitochondrial dysfunction. Downregulation of the sodium bicarbonate transporter (NBCe1) was a key finding with the cultured cells, but this was not seen in KO tissue [ 51 ].…”
Section: Gene Expression Changes In Slc4a11 Knock-outmentioning
confidence: 99%